Differential Transcriptional Regulation in Roots of Tomato Near-Isogenic Lines in Response to Rapid-Onset Water Stress - Arms, Erin M.; Yan, Zhanghang; St.Clair, Dina A. (Frontiers in Plant Science, 2017)
Cultivated tomato (Solanum lycopersicum L.) is susceptible to abiotic stresses, including drought and chilling stress, while its wild relative (S. habrochaites) exhibits tolerance too many abiotic stresses. Chilling roots to 6 °C induces rapid-onset water stress by impeding water movement from roots to shoots. Wild S. habrochaites responds to root chilling by closing stomata and maintaining shoot turgor, while cultivated tomato fails to close stomata and wilts. This phenotypic response (shoot turgor maintenance under root chilling) is controlled by a major QTL stm9 on chromosome 9 from S. habrochaites that was previously high-resolution mapped to a 0.32 cM region, but its effects on transcriptional regulation were unknown. Here we used paired near isogenic lines (NILs) differing only for the presence or absence of the S. habrochaites introgression containing stm9 in an otherwise S. lycopersicum background to investigate global transcriptional regulation in response to rapid-onset water stress induced by root chilling. NIL175 contains the S. habrochaites introgression and exhibits tolerance to root chilling stress, while NIL163 does not contain the introgression and is susceptible. RNA from roots of the two NILs was obtained at five time points during exposure to root chilling and mRNA-Seq performed. Differential expression analysis and hierarchical clustering of transcript levels were used to determine patterns of and changes in mRNA levels. Our results show that the transcriptional response of roots exposed to chilling stress is complex, with both overlapping and unique responses in tolerant and susceptible lines. In general, susceptible NIL 163 had a more complex transcriptional response to root chilling, while NIL175 exhibited a more targeted response to the imposed stress. Our evidence suggests that both the tolerant and susceptible NILs may be primed for response to root-chilling, with many of these response genes located on chromosome 9. Furthermore, serine/threonine kinase activity likely has an important role in the root chilling response of tolerant NIL175.